The effective removal of the metal ion Pb2+ from an aqueous solution by activated carbon prepared from macadamia nut shell: isotherm and thermodynamic studies - Meethai, Suphakan; Sikhamchin, Patcharin; Moonsri, Piyarut (Journal of Vocational Education in Agriculture, 2024)
The problem of lead heavy metal ion (Pb2+) contamination in both surface and underground water sources is a serious problem that affects the health of both people and animals that use the water sources for consumption and should be resolved urgently. A commonly used and effective method for removing heavy metal ions contaminated with water is by using an adsorbent process. Activated carbon is another adsorbent that has received interest in removing the heavy metal ion Pb2+. This research aims to study the characteristics and potential of activated carbon prepared from macadamia nut shells for removing lead ions from solutions. From the study, it was found that the prepared activated carbon has a surface with many micron-sized pores. Contains more than 80 % of the carbon element and has a pHpzc of 6 at conditions suitable for adsorption. The prepared activated carbon had the highest Pb2+ adsorption value of 37.03 mg g-1, able to remove more than 81% of Pb2+. The adsorption isotherm matched well with the Langmuir isotherm. The thermodynamic parameters DG < O and DH0 are equal to -6.39 kJ mol-1, indicating that this adsorption process is exothermic.